Student Speaking Anxiety, Causal Factors, and Recommendations: A Mixed Methods Research - Maida Norahmi; Cendikia Flory Aristia; Jackson Pasini Mairing (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
This study aims to analyze the level of speaking anxiety and factors causing it, as well as solutions based on students' perspectives at each level of anxiety. Using a mixed-methods research design with an explanatory sequential approach, quantitative data were collected through the Foreign Language Speaking Anxiety Questionnaire (FLSAQ) from 288 English Language Education students in batches of 2022, 2023, and 2024 at a public university in Palangka Raya. In-depth interviews, students were selected based on FLSAQ scores to represent high, medium, and low anxiety levels. Quantitative results showed that the majority of students were at a moderate level of anxiety (56.8%), while 18.3% showed high anxiety and 24.9% low. The results also showed that there were no significant differences in anxiety scores based on year of entry or class. Qualitative results showed students with high and medium anxiety experienced anxiety due to language competence (vocabulary and grammar), lack of speaking opportunities, negative experiences from the environment, and lack of preparation and confidence. Students with low anxiety generally have more active exposure to and use of English and better self-management strategies. The solutions that students expect include material preparation, independent practice, a supportive classroom atmosphere, and structured teaching strategies.